Analyzing and evaluating the metabolic and endocrine characteristics between lean and obese patients with polycystic ovary syndrome: a systemic review and meta-analysis - Zheng, Caiyu; Lin, Yuhao; Zhang, Zhijun; Ye, Jiawen; Lin, Yanmei; Tian, Jianqing (Frontiers in Endocrinology, 2025)
ObjectiveWe performed an extensive meta-analysis to compare hormone levels and metabolic attributes between obese PCOS (OP) and lean PCOS. The main outcome of the study was the differences in critical clinical parameters, including luteinizing hormone (LH), follicle-stimulating hormone (FSH), low-density lipoprotein (LDL) cholesterol levels, systolic and diastolic blood pressures (BPs), and fasting blood sugar (FBS) levels between lean and OP patients.MethodsThe present systematic review and meta-analysis was conducted in line with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and the protocol of this study was prospectively registered on PROSPERO (Registration No. CRD420251039530) to minimize reporting bias and enhance transparency. Briefly, a comprehensive search was performed on the PubMed, ISI Web of Science, Embase and Cochrane Central Register of Controlled Trials from inception to Apr. 1, 2025, in any language, with the exclusion of abstract-only publications.ResultsSeventy-three studies were analyzed. There were marked differences in metabolic indicators between the two groups. Lean PCOS participants had slightly lower levels of diastolic (SMD −0.56, 95% CI −0.79 to −0.33, p < 0.01) and systolic (SMD −0.58, 95% CI −0.80 to −0.36, p < 0.0003) BP relative to individuals with obese PCOS. They had lower levels of LDL (SMD −0.49, 95% CI −0.60 to −0.38, p < 0.01) and triglycerides (SMD −0.72, 95% CI −0.85 to −0.59, p < 0.01) than obese PCOS participants. The LH/FSH ratio in lean PCOS patients exceeded that in obese PCOS patients (SMD 0.23, 95% CI 0.07 to 0.40, p < 0.01). Moreover, the homeostasis model assessment of insulin resistance (HOMA-IR) was higher in obese PCOS patients (SMD -0.88, 95% CI -1.03 to -0.72, p < 0.01). However, there were no significant differences in anti-Müllerian hormone (AMH) level between the two groups.ConclusionThis meta-analysis provides valuable information regarding the profile of metabolic and endocrine characteristics between lean and obese PCOS patients. The specific treatment approach should be customized to each patient’s symptoms, fertility needs, and overall health. Further research is advocated to investigate the underlying mechanisms and to develop more targeted treatment strategies for different subgroups of PCOS patients.